Comparative Study of Levels and Curriculum in Education Systems of Indonesia and Australia - Bahri, Saiful; Salut Muhidin; Warta, Waska; Rahman, M. Abd.; Hayaturrohman, Hayaturrohman (Yayasan Indonesia Emerging Literacy Education, 2024)
This study compares the education systems in Indonesia and Australia, focusing on educational levels and curriculum. In Indonesia, the system is regulated by the Ministry of Education, Culture, Research, and Technology, with a 12-year compulsory education policy (from primary to secondary education) and the implementation of the latest curriculum, the Merdeka Curriculum, which emphasizes project-based learning and 21st-century skills. Religious education, however, is regulated by the Ministry of Religious Affairs. In Australia, with national standards from the Australian Curriculum, Assessment, and Reporting Authority, the education levels include Primary School, Junior Secondary School, and Senior High School, and the curriculum emphasizes general capabilities and cross-curriculum priorities. There is a significant difference: in Indonesia, at the primary and secondary levels, students are taught general national standard materials according to their level, whereas in Australia, at the senior high school level, students are taught according to their interests and expertise. However, both countries are committed to improving the quality of education. Indonesia focuses on access and technology, while Australia focuses on inclusivity and the professional development of teachers, with the aim of achieving high-quality education for all students.